Strukturne spremembe slovenskega kazenskega procesnega prava v zadnjih dvajsetih letih - Šugman, Katja (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2015)
The author analyses changes to Slovenian criminal procedure between 1994, when the first Slovenian code was adopted on the basis of the last consistent Yugoslavian model (enacted in 1967) to the present day. Thirteen amendments have already been made to the Code since 1994, and the author argues that it is the role of public prosecutor which has changed the most in this period: prosecutors are slowly but surely becoming the dominus litis of pre-trial procedure, thereby pushing the investigating judge ever further towards the role of a pre-trial judge and away from that of an inquisitorial investigator. This trend has been accompanied by a tendency to abolish the phase of judicial investigation completely and to introduce a unitary preliminary phase of criminal procedure led by the prosecutor. The basic principle of Slovenian procedure is still the so-called inquisitorial maxim, which therefore places it among other European inquisitorial systems, but gradually more adversarial solutions are being incorporated. Key examples of this trend are: the solution granting the suspect the right to be acquainted with his rights in the moment when the investigation becomes focused on him/her; in the introduction of selection mechanisms; in the adversarial model of a decision-making process of ordering investigating and coercive measures and consequently in the stronger activation of both parties at an earlier stage. The peak of this trend can be found in the introduction of plea negotiations. Increasingly, we see the adoption of legal solutions which put the defendant and the prosecutor in ever more active roles, making them more autonomous subjects with the power to resolve cases quicker than before, while the court becomes more passive, shrinking to the much more limited role of controlling their agreements.
Keywords: criminal law; kazenski postopek; kazensko pravo; kazensko pravosodje; procesno pravo